2022
DOI: 10.3389/fneur.2022.875893
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Stroke Care Processes and Development of Stroke Associated Pneumonia: A National Registry Cohort Study

Abstract: IntroductionTimely stroke care can result in significant improvements in stroke recovery. However, little is known about how stroke care processes relate to complications such as the development of stroke associated pneumonia (SAP). Here we investigated associations between stroke care processes, their timing and development of SAP.MethodsWe obtained patient-level data from the Sentinel Stroke National Audit Programme for all confirmed strokes between 1st April 2013 and 31st December 2018. SAP was identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(24 reference statements)
2
3
0
Order By: Relevance
“… 35 39 Therefore, early screening and rehabilitation of dysphagia can improve cough reflex, as well as reduce the aspiration and pneumonia incidence. 8 40 41 Our findings further confirm that dysphagia is an independent risk factor for pneumonia; further, the dysphagia rate in patients with pneumonia was about four times that of patients with normal swallowing function. Screening for swallowing function may reduce pneumonia incidence.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“… 35 39 Therefore, early screening and rehabilitation of dysphagia can improve cough reflex, as well as reduce the aspiration and pneumonia incidence. 8 40 41 Our findings further confirm that dysphagia is an independent risk factor for pneumonia; further, the dysphagia rate in patients with pneumonia was about four times that of patients with normal swallowing function. Screening for swallowing function may reduce pneumonia incidence.…”
Section: Discussionsupporting
confidence: 83%
“…Delays in screening and assessment were associated with pneumonia; further, pre–post comparison revealed that screening for swallowing disorders by nurses reduced the pneumonia rate and the length of hospital stay 35 39. Therefore, early screening and rehabilitation of dysphagia can improve cough reflex, as well as reduce the aspiration and pneumonia incidence 8 40 41. Our findings further confirm that dysphagia is an independent risk factor for pneumonia; further, the dysphagia rate in patients with pneumonia was about four times that of patients with normal swallowing function.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…15 Patients with ischaemic or haemorrhagic stroke were included, though patients at stroke units with less than a maximum of 150 patients in any of the 5-year period were excluded. 16 This was to better reflect International Journal of Stroke, 18 (9) patients experience at established specialist stroke units. Patients with a time from stroke onset to hospital admission greater than 24 h were also excluded, to avoid delayed stroke presentations where pneumonia may already have developed between stroke onset and admission.…”
Section: Settingmentioning
confidence: 99%